(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Software engineering, at its core, is a collaborative effort pushed by way of human ingenuity, verbal exchange, and innovation. This overview paper gives a comprehensive exploration of the pivotal position played by using human factors in software program engineering approaches.